Pilot Study: Long-Term Shedding of SARS-CoV-2 in Urine: A Threat for Dispersal in Wastewater - Baj, Andreina; Azzi, Lorenzo; Dalla Gasperina, Daniela; Genoni, Angelo; Tamborini, Antonio; Gambarini, Cinzia; Carcano, Giulio; Grossi, Paolo; Sessa, Fausto (Frontiers in Public Health, 2020)
Only four months after the beginning of SARS-CoV-2 epidemic, the world is facing a global pandemic due to a complex and insidious virus that today constantly poses new challenges. In this study we highlight a persistent shedding of SARS-CoV-2 RNA into the urine, even in patients with a negative nasopharyngeal swab and in patients considered recovered. What does it mean? Beside the fact that the kidney is a probable site of viral replication, the prolonged viral excretion is a matter of great concern for our drainage system contamination.